A review of the business case for workforce nutrition initiatives - Evert-jan Quak; Ayako Ebata; Inka Barnett (Frontiers in Public Health)
Undernutrition and malnutrition remain persistent challenges in low-and middle-income countries (LMICs), especially among workers in labour-intensive sectors. Workplace nutrition programmes (WNPs) have shown promising health benefits, but evidence on their business impact remains scarce—particularly in LMIC contexts. This review examines whether WNPs generate measurable business outcomes that could incentivise employer investment. Using a structured literature review (SLR) approach, we systematically analysed 24 relevant studies—10 systematic reviews and 14 empirical papers. Search terms targeted nutrition-related workplace interventions and business outcomes, including productivity, absenteeism, and return on investment. Searches were conducted across Scopus, ScienceDirect, Google Scholar, and grey literature sources. Studies were included if they assessed business-related outcomes of health or wellness interventions with nutrition components. Only four studies were based in LMICs; the remaining 20 were from high-income countries (HICs), underscoring a major evidence gap. Despite this, two main impact pathways emerged: (1) healthier diets improve workers’ concentration and energy, reducing absenteeism and saving costs; and (2) improved nutrition enhances motivation, productivity, and work quality, which may increase sales and revenue. The first pathway is more relevant to skilled workers who are harder to replace, unlike the easily replaceable labour force common in many LMIC industries. In the second pathway, while improved nutrition may boost productivity, structural barriers—such as limited bargaining power in global supply chains—can prevent these gains from leading to better pay for workers. This review outlines key pathways through which improved worker nutrition may benefit businesses and identifies critical gaps in the evidence. It also proposes outcome indicators relevant to private sector stakeholders in LMICs, helping to guide future empirical research.